2009
DOI: 10.1097/qai.0b013e3181a42bdf
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine Is Not Associated With HIV Serostatus or Antiretroviral Therapy in Women

Abstract: Background The effects of HIV serostatus and combination antiretroviral therapy (cART) on plasma homocysteine (Hcy) are uncertain. Methods Plasma Hcy was assayed in a cross-sectional study of 249 HIV-infected and 127 HIV-uninfected women at the Bronx Women’s Interagency HIV Study site. Results Mean plasma Hcy was 7.42 ± 2.68 in HIV-infected and 7.18 ± 2.66 µmol/L in HIV-uninfected women (P = 0.40). Hyperhomocysteinemia (defined as Hcy > 10 µmol/L) was seen in 16.9% and 13.4 % of HIV-infected and HIV-uninfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…Surprisingly, no significant association was found between Hcy levels and the use of ART by Guaraldi et al [64]. Additionally, plasma Hcy was not associated with HIV serostatus or use of ART in a cross-sectional study that found 16.9% of HHcy (>10 µmol/L) in HIV-infected individuals (n = 249) and 13.4% of HHcy in noninfected (n = 127) individuals [71]. In the study, the prevalence was 50% and 65%, respectively [54].…”
Section: Nac Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Surprisingly, no significant association was found between Hcy levels and the use of ART by Guaraldi et al [64]. Additionally, plasma Hcy was not associated with HIV serostatus or use of ART in a cross-sectional study that found 16.9% of HHcy (>10 µmol/L) in HIV-infected individuals (n = 249) and 13.4% of HHcy in noninfected (n = 127) individuals [71]. In the study, the prevalence was 50% and 65%, respectively [54].…”
Section: Nac Resultsmentioning
confidence: 84%
“…However, no significant correlations were observed between HHcy and length of exposure to HAART. In two articles [71,72], the reduced availability of folate was raised as a confounding factor in the association between HHcy and ART. In fact, before the advent of HAART, 20% and 10% of HIV-infected patients had low vitamin B12 and red blood cell folate concentrations, respectively; now, the prevalence of low vitamin B12 is significantly lower in patients receiving HAART (8.7% versus 27%); 22.5% with low vitamin B12 and 51.4% with low folate had HHcy (>17.5 µmol/L).…”
Section: Nac Resultsmentioning
confidence: 98%
“…A meta-analysis performed on outcome 1 indicated that the plasma Hcy levels in HIV-infected patients were 2.05 µmol/L higher than the plasma Hcy levels in uninfected controls (95%CI: 0.13-4.01, P < 0.01; [30] Norway 15/21 CS 9.2 ± 7.3 9.0 ± 5.0 ---Naisbitt et al [31] England 33/33 CS 11.9 ± 4.7 14.5 ± 5.6 ---Bernasconi et al [32] Swaziland 80/73 COS 7.6 ± 3.6 8. 2 Remacha et al [23] Spain 128/235 CS 7.5 ± 7.8 14.3 ± 12.9 6.2% control; -B12 368.6 ± 219 Raiszadeh et al [35] United Castagna et al [29] Müller et al [30] Naisbitt et al [31] Vilaseca et al [33] Bernasconi et al [32] Remacha et al [23] de Larrañaga et al [34] Raiszadeh et al [35] Vigano et al [36] Borges-Santos et al [38] Abdollahi et al [37] Deminice et al [39] Total (95%CI) …”
Section: Outcomementioning
confidence: 99%
“…Mercié et al [40] Larrañaga et al [34] Remacha et al [23] Martí-Carvajal et al [41] Currier et al [4] Raiszadeh et al [35] Coria-Ramirez et al [43] Total (95%CI) associated adverse metabolic effects [47,49] . However, a lack of data in the revised papers prevents us from determining the contributions of different drug classes and durations of ART on Hcy levels (Table 2).…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation